2021
DOI: 10.22541/au.161368667.78191317/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opening a next-generation black box: ecological trends for hundreds of species-like taxa uncovered within a single bacterial >99% 16S rRNA operational taxonomic unit

Abstract: Current knowledge on environmental distribution and taxon richness of free-living bacteria is mainly based on cultivation-independent investigations employing 16S rRNA gene sequencing methods. Yet, 16S rRNA genes are evolutionarily rather conserved, resulting in limited taxonomic and ecological resolutions provided by this marker. We used a faster evolving protein-encoding marker to reveal ecological patterns hidden within a single OTU defined by >99% 16S rRNA sequence similarity. The studied taxon, subclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The genera Brevundimonas , Aquirufa and Polynucleobacter even contain distinct species sharing completely identical 16S rRNA genes. Furthermore, a recent investigation revealed that most likely hundreds of described and undescribed Polynucleobacter species share 16S rRNA similarities >99 % [46].…”
Section: Phylogenymentioning
confidence: 99%
“…The genera Brevundimonas , Aquirufa and Polynucleobacter even contain distinct species sharing completely identical 16S rRNA genes. Furthermore, a recent investigation revealed that most likely hundreds of described and undescribed Polynucleobacter species share 16S rRNA similarities >99 % [46].…”
Section: Phylogenymentioning
confidence: 99%